ANALISIS PERBANDINGAN PENGHINDARAN PAJAK SEBELUM DAN SESUDAH REFORMASI PAJAK TAHUN 2008 - Risa, Nurma (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2016)
The purpose of this study is to give evidence that there is the difference about tax avoidance in the period before and after tax reformation in Indonesia (2006 ? 2013). Tax avoidance is measure with book-tax difference. The sample of this study is manufactured company listed in BEI. One sample t-test is used for hypothesis analysis. The result shows there is no difference in tax avoidance before and after tax reformation in Indonesia. This may be because the company will change its tax planning strategies, so that the company still doing tax avoidance with new regulations.